SIKAP DAN PERSEPSI KONSUMEN TERHADAP JERUK LOKAL DAN JERUK IMPOR DI PASAR MODERN KOTA BOGOR - Nafisah, Sarah Nur; Suharno, Suharno; Tinaprilla, Netti (Forum Agribisnis, 2014)
The trends within citrus consumption have shifted from consumption of local citrus to the imported citrus. The present research investigates th econsumer characteristics of citrus, the consumer purchasing decision process, Â and consumer attitude and perception towards local citruss and imported citruss. Adopting purposive sampling technique, 100 respondents were chosen among the population of citrus consumers in modern market in Bogor. The data was Â analyzed with descriptive analysis, multi attribute Fishbein model, and perceptual mapping. The results showed that the majority of consumers were productive age female ranging from 27 to 34 years, married, bachelor degree, housewife with 3-4 family members, and with more than Rp 4.000.000 income per month. For both citrus, taste and freshness are the most important attributes Local citrusâs attributes such as taste, size, juicy, availability, appearance, freshness, the level of maturity, and the texture of pulp, were believed as a good attribute. Meanwhile for imported citrus, the juicyness, appearance, freshness, the level of maturity, the texture of pulp,andthesalespromotion, were believedto be agoodattribute. The price of bothlocal citrus and imported citruswas not believed as a good attribute. The score of consumer attitude and perception toward local citrus were higher than that of imported citrus. This shows that generally the local citrusâ attribute in modern market Bogor City was perceived as good by the consumers. Due to that the local citrus agribusiness actors needs to maintain and improve the performance of local citrusâattribute in such a way that the consumer prefer local citrus than imported citrus.